Does corruption matter for the environment? Panel evidence from China - Xianchun Liao; Eyup Dogan; Jungho Baek (Kiel Institute for the World Economy (IfW), 2016)
This paper examines the income-energy-SO2 emissions nexus by taking a corruption variable into account. To that end, the panel cointegration methods are applied to 29 Chinese provinces over 1999-2012. The authors' empirical evidence shows that an increase in the number of anticorruption cases tends to drive down SO2 emissions in China. It is also found that income growth appears to have a beneficial effect on decreasing SO2 emissions over the past two decades. Finally, energy consumption is found to increase SO2 emissions.
Keywords: C23; Q56; 330; China; corruption; environment; EKC; panel; SO2